Penerapan Kertas Kerja Pemeriksaan (KKP) Op Schedule terhadap Audit Laporan Keuangan - Rosita Farhat; Munari Munari (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This research aims to analyze the application of the KKP top schedule in financial report audits. With a case study at Dony Firliawan's public accounting firm (KAP), this research identifies the benefits and challenges of using the top schedule KKP. This research uses a qualitative approach to understand the phenomena that occur. Data collection methods used in this research include interviews, observation, and document analysis. The research results show that the top schedule KKP helps auditors increase the efficiency and effectiveness of the audit process and increases the auditor's focus on high-risk areas in financial reports. However, this implementation also faces several challenges, such as time constraints, format complexity, and implementation consistency.